Fidèles au spectacle - Mélisande Leventopoulos (Conserveries Mémorielles)
In 1927, there was no collective body of catholic cinemagoers. However, the project of winning back the masses through the cinema led to the development of catholic investment in this field. Thus, answering the call of the Church, catholic missionary spectators appeared in the diocese of Paris. Cinemagoers were taught how to view different types of film and this initiation led, at the end of the 1930s, to the emergence of a catholic audience per se in Paris.